Downstream Processing of Xylitol from Oil Palm Empty Fruit Bunch Hydrolysate: Effects of Impurities from OPEFB Hydrolysate on Xylitol Crystalls - Made Tri Ari Penia Kresnowati; Faradiva Dwinta; Susi Zukriwati (Jurnal Teknik Kimia Indonesia)
Abstract. Oil palm empty fruit bunch (OPEFB) contains xylose that can be utilized as the raw material for xylitol production, for example via fermentation. Besides containing xylitol, the fermentation broth using OPEFB hydrolysate as the substrate also contains other metabolic products: ethanol, acetic acid, cell-biomass; left-over substrates: glucose, xylose, inorganic salts, and residue of OPEFB. Downstream processing of the fermentation broth is necessary to produce xylitol with high purity. This article presents the evaluation of downstream processing for xylitol production, which comprises centrifugation, activated carbon adsorption, evaporation, and crystallization. In particular the effects of impurities from OPEFB hydrolysate on xylitol crystal was evaluated. The results show that fermentation broth composition, as well as xylitol concentration, significantly affect the yield, purity, and whiteness index of the obtained xylitol crystal. Keywords: adsorption, centrifugation, crystallization, fermentation, xylitol. Abstrak. Proses Hilir Produksi Xilitol dari Hidrolisat Tandan Kosong Kelapa Sawit. Tandan kosong kelapa sawit (TKKS) mengandung xilosa yang dapat dimanfaatkan sebagai bahan baku pembuatan xilitol, misalnya melalui fermentasi. Selain mengandung xilitol, kaldu fermentasi yang memanfaatkan hidrolisat TKKS sebagai substrat juga mengandung produk metabolisme lainnya seperti etanol, asam asetat, biomassa sel; dan substrat sisa yaitu: glukosa, xilosa, garam anorganik, dan residu TKKS. Proses hilir kaldu fermentasi ini diperlukan untuk menghasilkan xilitol dengan kemurnian tinggi. Artikel ini menyajikan evaluasi awal proses hilir produksi xilitol, yang meliputi sentrifugasi, adsorpsi dengan karbon aktif, evaporasi, dan kristalisasi. Hasil penelitian menunjukkan bahwa komposisi kaldu fermentasi serta konsentrasi xilitol berpengaruh nyata terhadap rendemen, kemurnian, dan indeks keputihan kristal xilitol yang diperoleh. Keywords: adsorpsi, fermentasi, kristalisasi, sentrifugasi, xilitol.